Economic value of data flows - Foley, Paul,Aatif,Gemmell, Alexandra,Rys, Jonah,Vinciguerra, Chiara (Publications Office of the European Union, 2023)
Research examining the value, volume and trends of cloud based data flows is a complex exercise. A limited number of studies have succeeded in developing methodologies to map and monitor data flows, such as the study 'Mapping Data Flows' commissioned by the European Commission. But none have calculated the economic value of cloud data flows This study, which is part of the European Commission initiative 'The European Cloud Data Flow Monitoring', provides an innovative and replicable methodology to monitor, estimate and forecast to 2030 the value of cloud data flows within the EU, EFTA countries and the UK. Interviews were undertaken with 1,200 private and public sector enterprises in six EU27 Member States (Czech Republic, Germany, Greece, Poland, Spain and Sweden) to collect raw data and analyse the characteristics of enterprises adopting cloud services, their economic impacts as well as the one from cloud data flows. Results from interviews and other research undertaken by the study estimated that the total volume of cloud data flows in 2022 in the EU was 11.2 EX. The total economic value associated to cloud data flows in the EU in 2022 was 2.05 billion, meaning €183 million per EX of cloud data flows. The analytical framework for the study has developed tools for the continuous analysis of the volume of cloud data flows and their associated economic value up to 2030. This analytical framework could be used in the future to analyse and monitor data flow trends in terms of volume and economic value across and within the European Union to provide evidence in support of EU policy, trade and investment decisions.
10.2759/019969
Keywords: Graue Literatur; Amtliche Publikation; Elektronischer Datenaustausch; Cloud Computing; Wertschöpfung; EU-Staaten; EFTA-Staaten; Großbritannien; big data; cloud computing; innovation; economic consequence; investment; EU policy; type of business; trade policy; communications systems; information system; decision-making; Spain; Greece; Poland; Czechia; Sweden; Germany